2005
DOI: 10.4049/jimmunol.175.10.6311
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Survival of Fully MHC-Mismatched Islet Allografts by Targeting a Single Chemokine Receptor Pathway

Abstract: Chemokine receptor blockade can diminish the recruitment of host effector cells and prolong allograft survival, but little is known of the role of chemokine receptors in promoting host sensitization. We engrafted fully allogeneic islets into streptozotocin-treated normal mice or mice with the autosomal recessive paucity of lymph node T cell (plt) mutation; the latter lack secondary lymphoid expression of the CCR7 ligands, secondary lymphoid organ chemokine (CCL21) and EBV-induced molecule-1 ligand chemokine (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…Raised CXCL10 levels have been demonstrated after infection of mice with a number of pancreas-tropic viruses capable of triggering T1D in a mouse model, while neutralization of CXCL10 prevented T1D in this model (34). Likewise, CCL21a is able to drive the pancreatic recruitment of lymphocytes (35,36) and is required for islet transplant rejection (37). CCL21a appears to increase the binding of T cells to vascular endothelium and has been shown in blocking studies to be required for the entry of a diabetogenic islet-reactive CD8 T cell clone into the pancreas of NOD mice (38).…”
Section: Discussionmentioning
confidence: 92%
“…Raised CXCL10 levels have been demonstrated after infection of mice with a number of pancreas-tropic viruses capable of triggering T1D in a mouse model, while neutralization of CXCL10 prevented T1D in this model (34). Likewise, CCL21a is able to drive the pancreatic recruitment of lymphocytes (35,36) and is required for islet transplant rejection (37). CCL21a appears to increase the binding of T cells to vascular endothelium and has been shown in blocking studies to be required for the entry of a diabetogenic islet-reactive CD8 T cell clone into the pancreas of NOD mice (38).…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, several studies showed that a blockade of CCR7 or its ligands was effective in promoting graft survival in animal models of heart or islet allotransplantation. 19,20 Moreover, a study by Schlereth et al demonstrated that topical blockade of CCR7 significantly inhibited the development of allergic conjunctivitis by impairing the ability of ocular surface DCs to generate allergic immunity. 21 Hence, a reduction of CCR7 expression on APCs by hMSCs as shown in this study might account for one of the mechanisms of hMSCs in preventing immune responses in allotransplantation of the cornea or probably other organs.…”
Section: Discussionmentioning
confidence: 97%
“…In previous literature, the effect of targeting CCR7 or its ligands on solid-organ transplantation was assessed only in knockout models, but these studies demonstrated only limited prolongation of organ survival in the CCR7 Ϫ/Ϫ as well as plt Ϫ/Ϫ groups compared with wild-type mice (10,11,44,45). In contrast, the graft survival in CCL19-IgG-treated mice was superior to that reported for transplants in knockout mice in both models.…”
Section: Discussionmentioning
confidence: 99%